Investigating Pathology and Subtypes (H5 and H9) of Avian Influenza Virus (AIV) Circulating in Ducks, Layers and Broilers - Parvin, Dilruba; Sultana, Nazneen; Pervin, Munmun; Sultana, Sajeda; Bari, Abusaleh Mahfuzul; Khan, Mohammad Abu Hadi Noor Ali (Journal of the Bangladesh Agricultural University, 2025)
The avian influenza virus (AIV) is consistently ignited in chickens, ducks and broilers. This study was aimed to investigate the detailed pathology of AIV infected ducks, layer chicken, broilers, and pigeons and subtyping of hemagglutinin (HA) and neuraminidase (NA) genes of AIV to predict types of this virus prevailing in Bangladesh. A total of 32 birds were collected from live bird markets, CDIL (Dhaka), and layer farms. Layer chickens exhibited depression, cyanotic combs and wattles. Necropsy was performed; tissue samples were fixed and stained with hematoxylin and eosin, and examined under microscope. Grossly, the birds showed mild to moderate hemorrhages on tracheal mucosal, congested and consolidated lungs, hemorrhagic pancreas and mild congestion and hemorrhages throughout the body. Histopathology revealed widespread congestion and hemorrhages in the tracheal mucosa, lungs, pancreas, heart, and degenerated hepatic cords. Hemorrhages in pancreas, tracheal mucosa, comb, wattles and or shanks were characteristics. Viral RNA was extracted from tracheal tissues using the PureLink™ Viral RNA Mini Kit, and RT-PCR targeting M, HA, and NA genes of AIV were performed for subtype identification. Out of 32 birds examined, M protein gene specific RT-PCR amplification of 510bp fragment was detected in 18 cases. H5 gene specific RT-PCR found to amplify 499bp fragments in 2 ducks and 4-layer chickens and H9 gene specific (221bp) amplification was found in two broiler chickens. NA subtype gene amplification (1089 bp) revealed 8 birds yielding the expected amplicon. H5 subtype was predominant in ducks and layer chickens, while H9 subtype was detected in broilers. H5, H7, and H9 gene-specific amplification left undetected in 02 pigeons and 08 other birds. AI viruses were prevailing in the birds of live bird markets and it needs more emphasis to routinely sequence and sequence analysis of HA and NA genes of AI viruses to predict future emergence of any pandemic viruses of public health importance and designing its control strategies. J Bangladesh Agril Univ 23(4): 516–523, 2025